The Role of Government Politics and Law in Building Public Participation in Elections - Appe Hutauruk (Journal of Social Science, 2023)
The use of voting rights in a general election is the subjective right of citizens (people) who have qualified to vote, but from the aspect of the interests of the state and nation, it can be considered that the use of voting rights / voting rights of citizens in general elections, in essence is a form of responsibility to participate in the administration of government. However, at the current level of reality there is a tendency for people to experience "frustration" and "political lethargy" to exercise their sovereignty through the mechanism of elections. This fact is due to the fact that people feel that their aspirations cannot be accommodated after the general election and presidential election. In addition, there is the influence of pressure groups (especially groups that want the disintegration of the nation and the Unitary State of the Republic of Indonesia) so that people better abstain and become "white groups". Therefore, a directed and effective government legal policy is needed to increase legal awareness of citizens participating in exercising their active voting rights in general elections and presidential elections.